Computed tomographic quantitative evaluation of common bile duct size in normal dogs: A reference range study considering body weight - Kim, Yein; Kim, Sung-Soo; Kwon, Danbee; Im, Deokho; Lee, Kichang; Yoon, Hakyoung (Frontiers in Veterinary Science, 2023)
Introduction Common bile duct (CBD) measurements are important for the evaluation of biliary systemic disorders. However, in veterinary medicine, reference ranges for specific body weights (BW) and correlation between CBD diameter and BW have not been studied. This study aimed to establish normal reference ranges of CBD diameter for different BW groups and to analyse correlation between CBD diameter and BW in dogs without hepatobiliary disease. Additionally, normal reference ranges of CBD to aorta ratio (CBD: Ao ratio) were established which is not affected by BW. Methods CBD diameter was measured at three different sites: porta hepatis (PH), duodenal papilla (DP) level and mid-portion (Mid) between these points using computed tomography (CT) in 283 dogs without hepatobiliary disease. Results The reference range of CBD diameter at PH level: 1.69 ± 0.29 mm (Class 1; 1 kg ≤ BW < 5 kg), 1.92 ± 0.35 mm (Class 2; 5 kg ≤ BW < 10 kg), 2.20 ± 0.43 mm (Class 3; 10 kg ≤ BW < 15 kg), 2.79 ± 0.49 mm (Class 4; 15 kg ≤ BW < 30 kg); Mid-level: 2.06 ± 0.25 mm (Class 1), 2.43 ± 0.37 mm (Class 2), 2.74 ± 0.52 mm (Class 3), 3.14 ± 0.44 mm (Class 4); DP level: 2.33 ± 0.34 mm (Class 1), 2.90 ± 0.36 mm (Class 2), 3.35 ± 0.49 mm (Class 3), and 3.83 ± 0.50 mm (Class 4). There was a significant difference in CBD diameter at each level among all BW groups. Furthermore, BW and CBD diameter showed positive linear correlation at each level. We devised CBD: Ao ratio at each level that showed no significant difference between the different BW groups; PH level: 0.34 ± 0.05; Mid-level: 0.42 ± 0.06; DP level: 0.47 ± 0.06. Conclusion In conclusion, since the CBD diameter for each BW is significantly different, different normal reference ranges of CBD diameter should be applied for each BW, and the CBD: Ao ratio can be used regardless of the BW.